Building a "Better Life": The Transformative Effects of Adolescent Pregnancy and Parenting. (10th February 2015) - O'Brien Cherry, Colleen; Chumbler, Neale; Bute, Jennifer; Huff, Amber
Adolescent pregnancy is often described as a major concern in public health and is associated with negative outcomes for educational and career attainment. Our objective was to compare the future aspirations of pregnant and parenting adolescents and identify social or structural barriers that they experience in their daily lives using journal entries from pregnant and parenting adolescents. The journals, which served as primary data sources, were completed by 52 multi-ethnic pregnant and parenting adolescents aged 15 to 19 in Indiana. Both pregnant and parenting adolescents aspired to provide a "better life" for their children that included finishing school and obtaining a career. An emergent theme is that the experience of pregnancy and parenting is transformative and may invoke a positive refocusing of life aspirations for educational and career attainment. However, social stigma and barriers exist that make achieving educational and employment opportunities difficult. The study findings indicate that pregnant and parenting adolescents need strong social support networks and practical tools to help harness their motivation and transcend social and material barriers to achieve their goals and aspirations.